3D Mapping of the DMEK Detachment Area from OCT Scans of the Anterior Segment of the Eye – Clinical Applications - Kladny, Anne-Marie S.; Glatz, Andreas; Böhringer, Daniel; Zander, Daniel Bernhard; Lieberum, Judith-Lisa; Reinhard, Thomas; Wacker, Katrin (Klinische Monatsblätter für Augenheilkunde, 2024)
Graft detachment is the most common complication after Descemet membrane endothelial keratoplasty (DMEK). To assess the amount of graft detachment, precision is limited when using slit-lamp biomicroscopy. Detachment of DMEK grafts can be assessed automatically on anterior segment optical coherence tomography (AS OCT) images and allows visualization of the area and volume of detachment using 3D maps. This article provides an overview of its applications such as accurately assessing the course of natural graft attachment, identification of potential risk factors for detachment and evaluation of the long-term effect of graft detachment. The 3D map of DMEK detachment may support researchers and clinicians in precise quantification of the area and volume of graft detachment even in large data sets, and the intuitive, fast and reliable evaluation.
Keywords: anterior segment OCT; endothelial keratoplasty; Fuchsʼ endothelial corneal dystrophy; DMEK; graft detachment